MPN TOTAL COLIFORM PADA ES KRIM - Siti Raudah; Agus Joko Praptomo; Ananda Mey (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Ice cream is processed from raw milk ingredients, in the process of making ice cream dough will greatly determine the quality of the ice cream later. Many factors influence the quality, starting from raw materials, manufacturing processes, freezing processes, and so on. Water used in the manufacture of ice cream must be hygienic and meet sanitary standards. This study aims to determine the MPN Total Coliform description on ice cream sold in Samarinda Ulu District. The MPN method (Most Probable Number) is a method with a Presumptive Test and a Confirmed Test. This research was conducted at the UPTD Regional Health Laboratory of East Kalimantan Province in March 2017 with a sample of 25 ice creams from 25 sellers and the sampling technique used total sampling. The results showed total Coliform MPN results on ice cream in Samarinda Ulu, there were 25 samples examined and the results showed that 22 ice cream samples did not meet the quality requirements with a range of values> 1100 - 9.2 MPN / gr and ice cream that met 3 quality requirements. sample is <3.0 MPN / gr. While the quality requirements for ice cream determined by SNI No. 01-7388-2009 which is <3 MPN / gr